Investigating the impact of UV-C/H2O2 and sunlight/H2O2 on the removal of antibiotics, antibiotic resistance determinants and toxicity present in urban wastewater - G. Michael, Stella (2022)
This work aimed at exploring the impact of UV-C/H2O2 and sunlight/H2O2 processes, applied at pilot scale, on removing: (i) ciprofloxacin and sulfamethoxazole, (ii) cultivable Escherichia coli and Pseudomonas aeruginosa grown in the presence and absence of sub-minimal inhibitory concentrations of ciprofloxacin and sulfamethoxazole and (iii) the genes 16S rRNA and selected antibiotic resistance genes (ARGs) (i.e., sul1, blaCTX-M, qnrS, tetM, etc.) from urban wastewater. The major antibiotic transformation products (TPs) formed, were elucidated and the chronic toxicity of the whole effluent mixture against Vibrio fischeri was evaluated. The capability of the processes, in terms of the elimination of the antibiotics present in urban wastewater, varied among the two light sources used: both antibiotics were fully removed during UV-C/Η2Ο2, whereas only ciprofloxacin was removed during the sunlight/H2O2. The photo-transformation of the antibiotics led to the identification of 21 and 18 TPs of ciprofloxacin and sulfamethoxazole, respectively, while all of them retained their core moiety, responsible for the antibacterial activity. All the UV-C/H2O2-treated samples were found to be toxic, whereas the luminescence of V. fischeri was not inhibited when tested in the sunlight/H2O2-treated samples. During both processes, E. coli, P. aeruginosa and the colonies of these species still viable in the presence of antibiotics, were successfully inactivated to values below the detection limit. However, sunlight/H2O2 has not achieved complete disinfection, as regrowth of E. coli and P. aeruginosa colonies was observed after 48 h of storage of the treated effluent. Finally, none of the technologies tested was able to completely remove the target ARGs, confirming their inability to prevent the spread of resistance determinants to the environment.